Improving Teachers Self-Efficacy through Training: An Impact for the Freedom of Students Mathematical Thinking - Haninda Bharata; Sugeng Sutiarso (Universitas Syiah Kuala, 2021)
Teacher self-efficacy is an important component of teacher competence. At present, efforts to improve teacher competencies have not been carried out simultaneously for teacher activities in the classroom (open class) and outside the classroom (training). This quasi-experimental study aimed to examine the effectiveness of soft skills training and the practice of lesson study on improving mathematics teacher self-efficacy and describe the impact of teacher self-efficacy on the freedom of students' mathematical thinking. The study involved three mathematics teachers and 90 students from three different junior high school regions in Bandar Lampung, Indonesia (city center, semi-urban, and suburban). Data was collected through questionnaire, observation, and interview. The data were then analyzed descriptively. The effectiveness of soft skills training and the practice of lesson study on improving mathematics teachers self-efficacy was examined using Wilcoxon Test. The results showed the differences in the average teachers self-efficacy before and after participating in soft skills training and the practice of lesson study (with an increase of 0.82/high). The increase in teachers self-efficacy also positively affected the freedom of students mathematical thinking.